Investigating the level of Hba1c and insulin level in Î²-thalassemia patients - Mujiburrahman, Husnan; Santosa, Qodri; Setyono, Joko; Roestijawati, Nendyah; Rujito, Lantip (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2023)
Background: Î²-thalassemia is an inherited blood disorder characterized by reduced or no synthesis of Î² globin chain, resulting in chronic anemia, so blood transfusion is required as curative therapy. Repeated blood transfusions lead to iron overload that can lead to multiple organ damage, including pancreatic organs. Objective: This study aimed to describe HbA1c and insulin levels of Î²-thalassemia patients. The study also tested whether there was a significant difference in insulin and HbA1c levels among patients with different Î²-thalassemia categories.Â  Method: This research was an analytic observational study. The samples were taken by total sampling and involved 30 patients, and the examination was carried out using the patient's blood plasma. Result: The study found that samples had low HbA1c levels. There was no significant mean difference (p>0.05) between insulin and HbA1c in the mild, moderate, and severe clinical degree groups. There was no significant difference in average (p>0.05) insulin and HbA1c in the thalassemia sufferers with allele Î²+ and Î²0 types. Conclusion: There was a decrease in insulin and HbA1c in patients with Î²-thalassemia, which may be caused by damage pancreatic organ damage.